The Acquisition of English Indefinite Restrictive Relative Clauses by Lattakian Arabic Speakers - Shaheen, Buthaina (Forum for Linguistic Studies, 2025)
One of the goals of second language acquisition research is to contribute to the development of a theory that can answer intriguing issues related to the role of first language in development and the extent to which universal principles of linguistic organization (universal grammar) guide the development of second language learners’ mental grammars for the target language. This study homes in on contributing to this goal by investigating how speakers of Lattakian Syrian Arabic acquire English indefinite RRCs. Based on the well-known properties of restrictive relative clauses in English, the account that best fits the data of English is the traditional operator movement analysis, while for Lattakian Syrian Arabic a clitic left-dislocation account offers the best fit. In this study, learners of different proficiency levels (as measured by an independent proficiency test) completed a grammaticality judgement task, a guided gap-filling task and a translation task. Results show partial first language influence at early stages of learning and persistent influence in later stages of learning, but specifically on properties that involve uninterpretable features. The findings largely support the theoretical position that argues for fundamental differences in native speaker and L2 syntactic representations. The implications of these findings for theories of second language acquisition are considered.